Tomographic evaluation of dehyscences and fenestrations produced by post orthodontic patients. A review of literature - Benza, Rosa Maria (2019)
Dehiscences and fenestrations are commonly observed as a result of a secondary effect in orthodontic treatment. These characteristics are only visualized with high resolution images.  where thickness, depth and height are quantified. In addition, said images are taken by cone bean computed tomography, which is an specific tool to diagnose dehiscences and fenestration, due to its reliability and help in diagnosis of support tissue. The objective is to prevent bone defects after an appropiate treatment. The cone bean computed tomography (CBCT) is a useful tool to determine the prevalence of dehiscence and fenestration in post-orthodontic patients. That is why, the cone bean computer tomography must be included as a diagnostic assistance before the beginning of the orthodontic treatment with the purpose of avoiding bone defects which are caused by orthodontic movements like bucco-lingual displacement, retrusions and intrusions